Radiosensitivitas dan Keragaman Ubi Kayu (Manihot esculenta Crantz) Hasil Iradiasi Sinar Gamma - Maharani, Sadewi; Khumaida, Nurul; Syukur, Muhamad; Ardie, Sintho Wahyuning (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2015)
ABSTRACTHigh genetic variability is one of important determinants in successful breeding of clonally propagated crops such as cassava. Induced mutation, including mutagenesis using gamma irradiation, is one strategy to increase genetic variability. The objective of this research was to obtain information of lethal doses (LD20-LD50) from five cassava genotypes (Jame-jame, Ratim, UJ-5, Malang-4, and Adira-4), to analyze the variability, and to obtain potentially high yielding cassava mutant candidates. Cuttings of several cassava genotypes were irradiated by 0, 15, 30, 45, and 60 Gy gamma rays. The results showed that genotype Malang-4 had the lowest LD20 (7.53 Gy) and LD50 (18.47 Gy), while genotype Jame-jame had the highest LD20 (24.94 Gy) and LD50 (33.24 Gy). The highest phenotype variability was obtained in the cassava population irradiated by 15-30 Gy gamma rays. The highest phenotype variability was also determined by the source of tissue, i.e., cuttings from the middle stem resulted in the highest phenotype variability. This research found 32 high yielding potential candidate mutants.Keywords: gamma rays, LD20, LD50,mutant, mutation